A descriptive study of vancomycin usage at Red Cross War Memorial Children's Hospital, Cape Town - Greybe, Leonore (Department of Paediatrics and Child Health, 2024)
Background: Antimicrobial stewardship principles guide the clinical use of vancomycin, but paediatric vancomycin prescribing practices have not been evaluated in South Africa. Objectives: To document the use, prescribing practices and monitoring of intravenous vancomycin and the spectrum of bacteria isolated on microbiological culture in children treated with intravenous vancomycin during a 12-month period at Red Cross War Memorial Children's Hospital (RCWMCH). Methods: A retrospective audit of intravenous vancomycin use in children admitted to RCWMCH during 2019. Results: All 158 vancomycin prescription episodes for 143 children were included. Overall usage of intravenous vancomycin was 63 days of therapy/1000 patient days (IQR 38–72). The median starting dose was 15 mg/kg/dose (IQR 14 ̶ 15) and median daily dose was 45 mg/kg/day (IQR 43–60). Vancomycin was prescribed as empiric (127/158, 80%) and directed (31/158, 20%) treatment. The median duration of treatment for the directed group was longer than the empiric group (p=0.001). Only 65/98 (66%) episodes where vancomycin treatment exceeded three days had vancomycin serum trough concentrations performed, and only 16/65 (25%) of these samples were obtained before the fourth dose. Prolonged antibiotic treatment of 14 days or more was not associated with gram positive bacteria on culture (OR 1.02, 95% CI 0.17 ̶ 4.2). Conclusion: Prolonged empiric treatment and inappropriate vancomycin monitoring were problems associated with vancomycin prescriptions. Contribution: Our study identified multiple opportunities for improved vancomycin prescribing and monitoring. Further research and implementation of improved prescribing practices could contribute to the preservation of vancomycin as an effective antibiotic.